2023
DOI: 10.1111/plb.13502
|View full text |Cite
|
Sign up to set email alerts
|

Identification and fine mapping of a new bacterial blight resistance gene, Xa43(t), in Zhangpu wild rice (Oryza rufipogon)

Abstract: Bacterial blight (BB) is currently considered one of the most serious rice diseases and is caused by Xanthomonas oryzae pv. oryzae (Xoo). Numerous studies have shown that breeding resistant rice varieties is one of the most effective methods to prevent BB, and it is important to identify and isolate more BB resistance (R) genes from different rice resources.• Using a map-based approach, we identified a new QTL/gene, Xa43(t), from ZhangPu wild rice, which was highly resistant to the BB isolate PX099. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Zhang [33] demonstrated that the introduction of wild rice alleles into cultivated rice significantly improved yield under drought conditions. Similarly, Huang [34] found that some wild rice species possess genes that confer resistance to bacterial blight. Yuan [35] also showed that wild rice germplasms also contain genes related to cold tolerance.…”
Section: Discussionmentioning
confidence: 98%
“…Zhang [33] demonstrated that the introduction of wild rice alleles into cultivated rice significantly improved yield under drought conditions. Similarly, Huang [34] found that some wild rice species possess genes that confer resistance to bacterial blight. Yuan [35] also showed that wild rice germplasms also contain genes related to cold tolerance.…”
Section: Discussionmentioning
confidence: 98%
“…Zhang [28] demonstrated that the introduction of wild rice alleles into cultivated rice significantly improved yield under drought conditions. Similarly, Huang [29] found that some wild rice species possess genes that confer resistance to bacterial blight. Yuan [30] also showed that wild rice germplasm also contains genes related to cold tolerance.…”
Section: Discussionmentioning
confidence: 98%
“…Different rice varieties have multiple different BB resistance genes. The BB resistance gene Xa43 was recently identified in Zhangpu wild rice (Oryza rufipogon) (Huang et al, 2023). A new NLR disease resistance gene Xa47 has long-term resistance to rice BB disease (Lu et al, 2022b).…”
Section: Bacterial Blight Resistancementioning
confidence: 99%